2000
DOI: 10.1063/1.481308
|View full text |Cite
|
Sign up to set email alerts
|

Local density augmentation in attractive supercritical solutions: Inhomogeneous fluid approach

Abstract: Density-functional theory and Monte Carlo simulation for the surface structure and correlation functions of freely jointed Lennard-Jones polymeric fluids Structure of Lennard-Jones fluids confined in square nanoscale channels from density functional theory Local density augmentation in attractive supercritical solutions. III. How important is the solute-solvent interaction range?We study the local solute-solvent structure in supercritical solutions, using as a model system a dilute Lennard-Jones solute in a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 46 publications
1
44
0
Order By: Relevance
“…38 These data together with those for the UV absorption and emission of anthracene dissolved in CO 2 at the same temperature 39 have been analyzed by Egorov using the Attard procedure for inhomogeneous fluids. 40 He found that for the first solute it was almost unnecessary to invoke local density enhancement to account for the experimental results but for the other two a …”
Section: Spectroscopic and Collisional Behaviormentioning
confidence: 98%
See 1 more Smart Citation
“…38 These data together with those for the UV absorption and emission of anthracene dissolved in CO 2 at the same temperature 39 have been analyzed by Egorov using the Attard procedure for inhomogeneous fluids. 40 He found that for the first solute it was almost unnecessary to invoke local density enhancement to account for the experimental results but for the other two a …”
Section: Spectroscopic and Collisional Behaviormentioning
confidence: 98%
“…40 In Figure 7, we present the solvatochromic shift of the absorption and emision of anthracene as measured by Zhang et al 39 The data for T red ) 1.02 could be well-fitted with HHNC theory using P ) 6.0 and (σ 2 /σ 1 ) ) 1.7. The figure also illustrates the curve corresponding to P ) 3.6, which is the maximum value of P compatible with 2 /k calculated with thermodynamic information, as discussed in the next section.…”
Section: Spectroscopic and Collisional Behaviormentioning
confidence: 99%
“…A clever application is then created by letting the spherical inhomogeneity arise from a fluid particle fixed at the origin of coordinates, so that an n-body distribution function in the inhomogeneous liquid becomes an (n þ 1)-body distribution function in the original homogeneous system. Familiar approximations now made at the nominal two-body level produce far better results [11][12][13][14] than when made at the conventional two-body level in a homogeneous formulation.…”
Section: Introductionmentioning
confidence: 91%
“…Integral equations have been extensively used to study supercritical fluids and solvation properties. 1, [3][4][5][12][13][14][15][16][17][18][19][20][21] In most previous works on integral equations concerning the solvation of neutral nonpolar solutes, the influence of varying the diameters of the solute and solvent, as well as the interaction strength, has been examined in detail. 15,[18][19][20][21] In the present work, we consider varying another crucial parameter, namely the range of the solute-solvent interaction.…”
Section: Introductionmentioning
confidence: 99%